Marketing Channel Efficiency of Snakehead Fish (Channa striata) Caught In Kalinapu Village, Paju Epat District, East Barito Regency, Central Kalimantan Province - Mutia Apriliani; Idiannor Mahyudin; Achmad Syamsu Hidayat (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Snakehead fish (Channa striata) is a high-value freshwater fishery commodity produced by artisanal fishers in Kalinapu Village, Paju Epat District, East Barito Regency. The marketing system in this inland village faces geographic constraints, limited transportation infrastructure, and the absence of cold chain facilities, which contribute to high distribution costs and a weak bargaining position for fishers. This study aimed to: (1) analyze the marketing channel structure; (2) calculate marketing costs, marketing margins, and farmer's share for each channel; and (3) determine the most efficient marketing channel for snakehead fish in Kalinapu Village. The study was conducted from March to June 2026 using a descriptive quantitative approach. The sample comprised 25 respondents selected by census and snowball sampling methods, consisting of 10 active fishers, 2 collectors, 1 wholesaler, 2 retailers, and 10 end consumers. Data were analyzed using marketing cost analysis, marketing margin analysis, farmer's share, and marketing efficiency ratio (Ep) based on Soekartawi (2002) and Kohls and Uhl (2002). The results showed that three marketing channels exist in Kalinapu Village. Marketing efficiency values were: Channel I (32.71%), Channel II (25.04%), and Channel III (28.78%), all classified as efficient (Ep ≤50%). Channel II, comprising fisher–collector Khusasi–retailer–consumer, was the most efficient channel with the lowest marketing costs (Rp15,024/kg) and a stable, routine distribution pattern. Channel III, which involved a wholesaler and bulk purchasing, yielded the highest farmer’s share (60%) despite involving more intermediaries, due to economies of scale in distribution